Brucella Septic Arthritis: Case Reports and Review of the Literature - Fatehi Elnour Elzein; Nisreen Sherbeeni (Case Reports in Infectious Diseases)
Brucellosis is one of the commonest zoonotic infections worldwide. The disease is endemic in Saudi Arabia, the Middle East, and the Mediterranean area. Osteoarticular involvement is a frequent manifestation of brucellosis. It tends to involve the sacroiliac joints more commonly; however, spondylitis and peripheral arthritis are increasingly reported. Brucellosis can be overlooked especially in the presence of companion bacteria. Hence, it should be suspected in all patients with septic arthritis in endemic areas or in patients visiting such areas.